A novel electronic patient-reported outcome delivery system to implement health-related quality of life measures in routine clinical care: An analysis of 5 years of experience - Tymms, Kathleen; O'Sullivan, Catherine; Smith, Tegan; Littlejohn, Geoffrey; Freeman, Tim; Hoffman, David; Segelov, Dana; Griffiths, Hedley; Ciciriello, Sabina; Youssef, Peter; Mathers, David; Deakin, Claire T (Frontiers in Digital Health, 2023)
OBJECTIVE: To develop a simple and secure technological solution to incorporate patient-reported outcomes (PROs) into routine clinical care. METHODS: A novel ePRO questionnaire delivery system was developed by Software for Specialists (S4S) in partnership with OPAL Rheumatology. Validated questionnaires were sent from the patient’s electronic medical record (EMR) (Audit4) and delivered to the patient’s email address or completed in the clinic waiting room using a smart device (in-practice). Completed questionnaires were encrypted and returned to the patient’s Audit4. Deidentified clinical data was extracted and aggregated across all sites. Data collected between April 2016-Dec 2020 were analysed descriptively. RESULTS: Between April 2016 to Dec 2020, 221,352 Functional Assessment of Chronic Illness Therapy Fatigue (FACIT-F), Patient Health Questionnaire-2 (PHQ-2) and/or HealthCare Resource Utilization (HCRU) questionnaires were sent from 39 of 42 contributing clinics (93%) to patients with RA, AS, PsA lupus or GCA. 85% of questionnaires were delivered via email and 15% in-practice. Overall, 85% of patients completed at least one questionnaire, and of all questionnaires sent, 73% were completed. Females were more likely to engage with the questionnaires than males (87% vs 81%), and older patients were slightly more likely to complete all questionnaires delivered. CONCLUSIONS: The novel Audit4 ePRO delivery system is an effective tool for incorporating PROs into routine clinical care. The data generated provides a unique opportunity to understand the full burden of disease for patients in the real-world setting and the impact of interventions.